Nursing the sepsis patient - part 1. Issue 8 (2nd August 2020) - Foreman, Emma
ABSTRACT: This two-part article aims to provide the knowledge and understanding for nurses to gain the confidence necessary to provide care for patients with sepsis in a critical care environment. It includes a critical care framework which can be utilised to implement the nursing interventions and assessments which are necessary to provide holistic nursing care to these patients.